The Extensor Mechanism: Imaging and Intervention - McMahon, Colm J.; Ramappa, Arun; Lee, Kenneth (Seminars in Musculoskeletal Radiology, 2017)
We present an overview of imaging and intervention of the extensor mechanism of the knee. Particular focus is placed on the evaluation of patellofemoral tracking disorders, patellar and quadriceps tendinosis and tears, patellar fracture, lateral patellar condyle patellar friction syndrome, and prepatellar bursitis. Anatomical and biomechanical factors contributing to these disorders are considered. Imaging evaluation is presented in a clinical context, and therapeutic options for these disorders are discussed. Image-guided therapy options for symptomatic patellar tendinosis are also described and illustrated.
Keywords: patellofemoral pain syndrome; patellar ligament; patellar dislocation; tendinopathy; bursitis